South African performance and archives of memory. - Hutchison, Yvette (Theatre Theory Practice Performance MUP., 2015)
This book argues that memory functions as a key element in contemporary South African re-imagining of historical events and in constructing new definitions of national and personal identity. It compares two ways in which memory is embodied: in repertoires of practices, songs, dance, rituals, and in material archives, texts, documents, buildings.